Analysis of Environmental Literacy in Students of the Social Studies Study Program UIN Kiai Haji Achmad Siddiq Jember: Analisis Literasi Lingkungan Pada Mahasiswa Program Studi Tadris IPS UIN Kiai Haji Achmad Siddiq Jember - Rachma Dini Fitria; Moh Barirul Umam (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to understand the level of environmental literacy among students in the Social Studies Education Program at UIN Kiai Haji Achmad Siddiq Jember who have completed the course